Employee satisfaction of commercial banks: The case of North Cyprus - Hoshi, Sanaz (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2014)
ABSTRACT: The aim of current study is to examine employee’s satisfaction regarding their positions at different structured banks, including private, public, foreign, and domestic banks in Northern Cyprus and how different factors affect the level of employee’s satisfaction. This survey characterizes the factors which create the job satisfaction. The factors are related with managers, rewarding, reorganization, salary, promotion, job security and relation in working environment. Frequency of the results which created by SPSS shows that there is a positive relationship between the level of job satisfaction and reward, salary, security of job, promotional opportunities and good relationship between the co-workers. The results of the research also indicate that most of the bank‘s employees in banking sector are satisfied with their job. Five point likert scale questionnaires framed and distributed among bank’s employees of North Cyprus personally, however only 154 out of 190 questionnaires which received back. Keywords: Employee satisfaction, Job satisfaction, Job security, salary, Promotional opportunities. ………………………………………………………………………………………………………………………………………………………………………………………………………… ÖZ: Bu çalışmanın amacı, Kuzey Kıbrıs’ta ki kamu, yerel ve yabancı bankalarda farklı pozisyonlarda çalışan banka memurlarının memnuniyetini ve farklı faktörlerin personel memnuniyet sevisiyesini nasıl etkilediğini incelemektir. Bu anket çalışmasında, iş memnuniyetini oluşturan faktörler tanımlanmaya çalışılmıştır. Bu faktörler, yöneticiler, ödüller, reorganizasyon, maaş, terfi, iş güvenliği ve iş ortamındaki ilişkeler ile ilgilidir. SPSS programıyla yaratılmış olan sonuç sıklık dağılımları, iş memnuniyet seviyesi ile ödül, maaş, iş güvenliği, terfi ve iş ortamındaki iyi ilişkiler arasında pozitif ilişki olduğunu ortaya çıkarmıştır. Bu çalışmanın sonuçları ayrıca, bankacılık sektöründe çalışanların çoğunun işlerinden memnun olduğunu göstermektedir. Beş noktalı Likert ölçek modeliyle hazırlanmış anket, Kuzey Kıbrıs’ta ki 190 banka personeline elden dağıtılmış ancak 154 tane geri dönüş olmuştur. Anahtar Kelimeler: Personel memnuniyeti, iş memnuniyeti, ticari bankalar, iş güvenliği, maaş, terfi fırsatları, çalışanlar arasındaki ilişkiler.
Master of Science in Banking and Finance. Thesis (M.S.)--Eastern Mediterranean University, Faculty of Business and Economics, Dept. of Banking and Finance, 2014. Supervisor: Assoc. Prof. Dr. Nesrin Özataç.
Keywords: Banking and Finance; Banks and Banking - Commercial Banks - Cyprus, North; Bank Employees - Satisfaction - Cyprus, North; Employee motivation - Banks - Cyprus, North; Employee Satisfaction, Job Satisfaction, Job Security, Salary, Promotional Opportunities